2006
DOI: 10.1037/0022-3514.90.1.94
|View full text |Cite
|
Sign up to set email alerts
|

When fiends become friends: The need to belong and perceptions of personal and group discrimination.

Abstract: The present article examines the role that the need to belong (NTB) plays in people's judgments of personal and group discrimination and in the attributions people make for potentially discriminatory evaluations. The authors hypothesized that the NTB motivates people to conclude that (a) whereas they rarely experience personal discrimination, (b) their fellow in-group members do experience discrimination. In Study 1, people high in the NTB reported experiencing lower than average levels of personal and higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 107 publications
1
41
0
1
Order By: Relevance
“…In sum, across three studies that utilized different methods (i.e., correlational and experimental) and tapped different aspects of forgiveness (dispositional forgiveness, forgiveness of hypothetical offenses, and state forgiveness for past offenses), we consistently found that the need to belong was negatively associated with forgiveness. Taken together, these studies break new ground by linking the need to belong with how people respond to interpersonal transgressions and contribute to the literature on how this fundamental motivation relates to important constructs in social psychology (e.g., Carvallo & Pelham, 2006;DeWall et al, 2008;Mellor et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In sum, across three studies that utilized different methods (i.e., correlational and experimental) and tapped different aspects of forgiveness (dispositional forgiveness, forgiveness of hypothetical offenses, and state forgiveness for past offenses), we consistently found that the need to belong was negatively associated with forgiveness. Taken together, these studies break new ground by linking the need to belong with how people respond to interpersonal transgressions and contribute to the literature on how this fundamental motivation relates to important constructs in social psychology (e.g., Carvallo & Pelham, 2006;DeWall et al, 2008;Mellor et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have invoked the need to belong in research on the personal-group discrimination discrepancy (Carvallo & Pelham, 2006), dismissing avoidant attachment style (Carvallo & Gabriel, 2006), sensitivity to social cues (Pickett, Gardner, & Knowles, 2004), self-regulatory performance (DeWall, Baumeister, & Vohs, 2008), suicide (Joiner, Hollar, & Van Orden, 2006), cooperation in public goods dilemmas (De Cremer & Leonardelli, 2003), life and relationship satisfaction (Mellor, Stokes, Firth, Hayashi, & Cummins, 2008), and homesickness (Watt & Badger, 2009). In the present article, we seek to expand on the existing literature by linking the need to belong with interpersonal forgiveness.…”
Section: Need To Belong: Theory and Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Research shows that participants are strongly influenced by information about intent and harm; for example, people are much more likely to make an attribution of discrimination if there is information that the actor intended to discriminate and/ or that the target experienced material or emotional harm (Swim, Scott, Sechrist, Campbell, & Stangor, 2003). Minorities who identify strongly with their ingroup are more likely to make attributions to discrimination (Sellers, & Shelton, 2003), but this may be counterbalanced by their motivation to fit in with other people more generally (Carvallo and Pelham (2006). Based on this research, we might expect that men who strongly identify with being gay will be more likely to make attributions of discrimination (because they are more alert to There are therefore some interesting parallels between the experimental and qualitative literatures, despite their methodological and ontological differences.…”
Section: Attributing And/ or Constructing Discriminationmentioning
confidence: 99%
“…This particular subscale has been used by many researchers as a measure of group identifi cation (Carvallo & Pelham, 2006;Chen, Chen, & Shaw, 2004;Eccleston & Major, 2006;Sellers, Rowley, Chavous, Shelton, & Smith, 1997;Vorauer & Turpie, 2004). The subscale conceptualizes identity as the importance of the group to self-concept and self-defi nition and is often recognized as conceptually tapping identifi cation rather than self-esteem (Ahlering, 2003;Branscombe, Schmitt, & Harvey, 1999;Cassidy, O'Connor, Howe, & Warden, 2004), serving as an explicit measure of the importance of collective identity (Ashmore, Deaux, & McLaughlin-Volpe, 2004).…”
Section: National Identifi Cationmentioning
confidence: 99%